PERKEMBANGAN OBJEK WISATA UMBUL SEWU DAN PENGARUHNYA TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT PENGGING DAN SEKITAR - Cahyaningrum, Octavi Rizky (Candi)
ABSTRACT This study aims to know : (1) the builts backround of Umbul Sewu as a tourism object (2)  the management of Umbul Sewu tourism (3) development of Umbul Sewu tourism (4) the influence of Umbul Sewu tourism against social economy life in Pengging community and around. This kind of study is descriptive qualitative. In this study used single spikes case studies that is target of study have been restricted, determined and also  centralized in one location that has its own character. The source of data that used are object, place, phenomenon, and documents. The sampling techniques used purposive sampling that is sampling based on the study objectives, where the researcher select the informant who considered issues in depth and also can be trusted. In this study, to find the data validity used two trianggulation technique that are dara trianggulation and method trianggulation. The data analysis technique that used is interactive analysis that is analysis proccess that moved between three components which includes data reduction, data presentment and verivication/inferences. This study can be concluded : (1) the builts backround of Umbul Sewu as a tourism object because the advantages of Pengging in tourism potential and the ease of its transportation (2) the manager develop Umbul Sewu with the family tourism concept which combine between swimming pool and restaurant. Umbul sewu is a tourism object that run by individuals PT. Umbul sewu are not cooperate with the Boyolali Department of Tourism and Culture but Umbul sewu only remit the tax to local government. (3) there is development in Umbul Sewu, slightly increase and the addition of a swimming pool as many as 3 pieces and gazebo as many as 12 pieces, an increase of visitors each year, this is due to the promotional efforts are always enhanced by the manager of Umbul Sewu. (4) The existence of Umbul Sewu tourism spot influence to the surrounding society, a change in the social life of the society such as changing the status of the unemployed had become employed. While the impact in the economic field was a very large increase in financial income and also increase the economic life in Pengging community and around.